An Analysis of the Communication of Organizational Knowledge Along Workflows at the University of West Georgia - Nelson, Harry Jacob, II (My University, 2018)
Faculty and staff morale at the modern university is often negatively affected by the corporatization of the university system. Part of the issue is that bureaucratic governance and collegial governance are brought into conflict in an organizational structure that does not easily reconcile these two methods of organizational control. One consequence of this situation is that the staff who directly serve the faculty do not have the resources to do so effectively. Specifically, they do not have quick enough access to the expert information from the bureaucratic units of the institution thereby increasing the occurrence of serious administrative errors, which in turn causes more dissatisfaction. This project demonstrates the need for the development of a decision tree and a knowledge base for ground-level, academic-department staff at the University of West Georgia (UWG). A decision tree would provide the ground-level university staff a help desk personnel functionality as a means to alleviate conflict between bureaucracy and collegiality. It could also reduce the demands on business office staff and improve the efficiency of workflows, while assisting in the development of more expertly informed collegial decisions. This project probes for qualitative data that can be used to develop the underlying, organizational structure and some significant initial content of a decision tree and knowledge base. It also develops a data set that can be used to examine the role of knowledge sharing between a university’s business office staff and the ground-level department staff, as it affects faculty attitudes toward corporate style governance. Since the processes related to this development involve workflows that separate bureaucratic expertise from departmental staff, the survey in this study primarily focused on university organization, policy and procedure, and the internal attitudes and perceptions about knowledge sharing along three specific workflows - the budget amendment process, the hiring of new staff positions, and the completion of non-routine purchases. This study also developed a foundation for future comparative studies of similar universities and government institutions. -- Keywords: University Bureaucracy; Academic Staff; Staff; Faculty; Bureaucracy; Business Office;
Keywords: Dissertations, Academic--United States; Public administration; Bureaucracy; Universities and colleges; Universities and colleges--Administration; Universities and colleges--Finance; Universities and colleges--Faculty; University of West Georgia